2012
DOI: 10.4196/kjpp.2012.16.6.387
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effect ofCyperi rhizomaandCorydalis tuberExtracts on Neuropathic Pain in Rats

Abstract: In this study, we examined the antinociceptive effect of Cyperi rhizoma (CR) and Corydalis tuber (CT) extracts using a chronic constriction injury-induced neuropathic pain rat model. After the ligation of sciatic nerve, neuropathic pain behavior such as mechanical allodynia and thermal hyperalgesia were rapidly induced and maintained for 1 month. Repeated treatment of CR or CT (per oral, 10 or 30 mg/kg, twice a day) was performed either in induction (day 0∼ 5) or maintenance (day 14∼ 19) period of neuropathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Also these studies report large variations with respect to number of administrations (either single, 3 days or 5 days administration) and dosage (ranging from 30 mg/kg to 20 g/kg). Furthermore none of these studies addressed the mechanism of YHS effect [ 7 – 10 ]. YHS is known to contain several alkaloids [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also these studies report large variations with respect to number of administrations (either single, 3 days or 5 days administration) and dosage (ranging from 30 mg/kg to 20 g/kg). Furthermore none of these studies addressed the mechanism of YHS effect [ 7 – 10 ]. YHS is known to contain several alkaloids [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang) is a perennial herb in the Papaveraceae family and has been used in traditional medicine on several disease5. Recently we have revealed that repetitive oral treatments of the extract from CT during the induction phase (day 0–5 after surgery) significantly alleviate chronic constriction injury (CCI)-induced MA, but not TH and reduce increase of spinal pNR1 in rats6. Levo-tetrahydropalmatine (l-THP) is one of active ingredient from Corydalis tuber and has an analgesic effects in several pain7891011.…”
mentioning
confidence: 99%
“…Meanwhile, Radix linderae can effectively alleviate inflammation (Chen et al ., ). Rhizoma Corydalis may be useful to alleviate neuropathic pain (Choi et al ., ). Rhizoma Corydalis might act on opioid, γ‐aminobutyric acid (GABA) or dopamine receptors and thus alleviate painful conditions such as headache, chest pain, epigastric pain, abdominal pain and backache (Yuan et al ., ).…”
Section: Discussionmentioning
confidence: 97%